(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Nephrotoxicity remains a common untoward effect of cisplatin therapy with limited effective chemopreventive options available till date. This study aims to evaluate the possible chemopreventive effect and mechanism(s) of action of 2 mgkg-1 and 5 mgkg-1 of Tadalafil in cisplatin-induced nephrotoxic rats. In this study, twenty-five male Wistar rats were randomly divided into five groups (n = 5 rats per group) and daily pretreated with oral doses of distilled water (10 mLkg-1), ascorbic acid (100 mgkg-1), Tadalafil (2 mgkg-1 and 5 mgkg-1) for 7 days before cisplatin (5 mgkg-1, intraperitoneal) was administered. 72 hours post-cisplatin injections, rats were sacrificed humanely and blood samples for serum electrolytes, urea and creatinine and renal tissues for reduced glutathione (GSH), superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px) and malonialdehyde dehydrogenase (MAD) assays and histopathology were collected. Results showed that cisplatin injection caused significant decreases in the serum sodium (Na+), potassium (K+), bicarbonate (HCO3-), calcium (Ca2+), phosphate (PO42-) and concomitant significant increases in the serum urea and creatinine levels. In addition, there were significant decreases in the renal tissue GSH, SOD, CAT and increased MAD and GSH-Px levels which were corroborated by histopathological features of tubulonephritis. However, these histo-biochemical alterations were significantly attenuated by ascorbic acid and Tadalafil pretreatments. Overall, results of this study showed the chemopreventive potential of Tadalafil against cisplatin-induced nephrotoxicity which was possibly mediated via antioxidant and anti-lipoperoxidation mechanisms.